Increased Oxygen Saturation through Deep Breathing Exercise and Active Range of Motion in Congestive Heart Failure Patients - Novita Nirmalasari (Alma Ata University Press, 2020)
Dsypnea is a clinical manifestation of CHF due to pulmonary function failure. The accumulation of fluid in the alveoli makes the heart unable to pump with the maximum. The changes that occur in the respiratory muscles make an increase from the sensation of dyspnea. This results in increased respiratory rate, blood pressure and pulse and decreased oxygen saturation, This is an important factor affecting the quality of life of patients. Pharmacologic and nonpharmacologic management is performed to maintain physical stability, avoid behaviors that can aggravate the condition and detect early symptoms of worsening heart failure. Deep breathing exercise and active range of motion is one of the non-pharmacological interventions to reduce breathing and increase respiratory muscle. The purpose of this study was to identification oxygen saturation after deep breathing exercise and active range of motion. The type of research used is quasi experimental research involving 16 respondents with purposive sampling technique. Deep breathing exercise and active range of motion performed 3 times a day for 3 days. The measuring instrument used is pulse oximetry. Data analysis using paired ttest test. The results showed an increase in oxygen saturation of 1.69%. This shows the effect of deep breathing exercise intervention and active range of motion on oxygen saturation (p=0,000, α <0.05). The exercise will increase oxygenation requirements due to increased movement of the respiratory and diaphragm muscles resulting in an increase in tidal volume, decreased functional residual capacity and an optimal increase in oxygen intake. This research suggests that deep breathing exercise and active range of motion interventions can be used as self-care nursing interventions. Further research can add measured variables and use random samples.